KINERJA GURU DITINJAU DARI MASA KERJA DI LEMBAGA PAUD GUGUS 3 KECAMATAN SELAPARANG - Izza Arisna; Muazar Habibi; Abdul Kadir Jaelani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher performance is a key factor in determining the quality of learning in early childhood education and may be influenced by teachers’ years of service. This study aimed to examine differences in teacher performance based on years of service among Early Childhood Education (PAUD) teachers in Cluster 3, Selaparang District. A quantitative research design with a survey approach was employed. The study involved 35 teachers from seven PAUD institutions, selected using a total sampling technique. Data were collected through a questionnaire consisting of 30 validated statement items and analyzed using descriptive statistics, normality and homogeneity tests, followed by a One-Way Analysis of Variance (ANOVA). The descriptive findings indicated that teachers with 16–20 years of service obtained the highest mean performance score, while those with 1–5 years of service had the lowest mean score. However, the One-Way ANOVA results showed no statistically significant difference in teacher performance among the different years-of-service groups (F = 1.539; p = 0.216 > 0.05). These findings suggest that years of service do not significantly influence teacher performance among PAUD teachers in Cluster 3, Selaparang District. Therefore, the null hypothesis (H₀) was accepted, while the alternative hypothesis (H₁) was rejected. This study implies that factors other than years of service may play a more substantial role in determining teacher performance and should be considered in future research and professional development programs.